Parkett : the Parkett series with contemporary artists. (Zürich : Parkett-Verlag, 2000)
Table of Content : 4REAL – Jeremy Deller and the Uses of Art by Greg Hilty ; Chuck Close Distances and Faces of the Moon by Francine Prose Raster + Vector = Animation ; Squared by Richard Shiff Putting English on the Stroke, Chuck Close in Conversation with Bice Curiger ; Diana Thater Come Closer – On the Intimacy of Vision in the Art of Diana Thater by Sara Arrhenius ; Art Remembers the Animal by Regina Haslinger Water, Sun and Thinking Bodies by Jeremy Gilbert-Rolfe ; Luc Tuymans Mirrorman by Laura Hoptman ; Painting on the Edge by Gerardo Mosquera ; In the Dark Regions ofthe World, Luc Tuyman’s recent paintings by Hans Rudolf Reust ; Shirana Shabazi, Insert The Body in the Library by Howard Singerman ; Thierry de Duve, A Conversation, Les Infos du Paradis by Cay Sophie Rabinowitz ; The Technology We Deserve, Cumulus from America by Frazer Ward ; Art, Utopia and the Media, Thoughts on the Jahrbuch für Künste und Apparate, Cumulus from Europe by Hans Ulrich Reck
When, at the end of the sixties, Chuck Close painted a reclining nude over 20 feet long in minutely detailed verisimilitude as well as faces of unprecedented size and exactitude, he challenged the visual practice of the art-viewing public.Although breaking out of the confines of convention as many others did at the time, Chuck Close still remained faithful to painting and the classical genres of the nude and portraiture. Stubborn insistence and a very long path traveled in literally the tiniest steps have staked out an exceptionally fertile land, as seen in the present volume. Close confronts the picture as monument with its structural dissolution, its de-composition and its treatment as playful experiment. Photographs have always been the starting point of his painterly excursions and have recently also become the substance of his art through forays into the venerable technique of the daguerreotype (also used in his edition for Parkett). (editorial by publisher)
boek
Keywords: Close, Chuck; Thater, Diana; Tuymans, Luc